Proinflammatory Stimuli Enhance Phagocytosis of Apoptotic Cells by Neutrophil Granulocytes - Hellberg, Lars (Hindawi Publishing Corporation, 2011)
Recently, we have reported that, in addition to macrophages, also neutrophil granulocytes can phagocytose apoptotic neutrophils. Based on this finding, we hypothesized that “cannibalistic” neutrophils at sites of acute infection/inflammation play a major role in the clearance of apoptotic neutrophils. Since at sites of infection/inflammation neutrophils are exposed to microbial constituents and proinflammatory cytokines, in the present study we analyzed the effect of TLR-ligands and cytokines on the ability of neutrophils to phagocytose apoptotic cells in vitro. We observed that exposure to ligands of TLR2 (Malp2, Pam3CSK4), TLR4 (LPS), TLR7/TLR8 (R848), and TLR9 (ODN 2006) led to increased phagocytosis of apoptotic cells by neutrophils. In addition, proinflammatory cytokines such as TNF and GM-CSF strongly enhanced the uptake of apoptotic cells by neutrophils. These results support the hypothesis that neutrophils acquire the ability to phagocytose apoptotic cells at sites of acute infection/inflammation and thereby can contribute to the resolution of inflammation.